Two-component polyurethane adhesive

By using two-component fire protection polyurethane glue combined with aluminum hydroxide filling, the problems of bonding strength, weather resistance and fire protection in the battery pack of electric vehicles are solved, and efficient thermal conductivity and structural strength are achieved.

JP2025510408AInactive Publication Date: 2025-04-14DUPONT TECH (SHANGHAI) CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025501755
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-25
Publication Date
2025-04-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high strength, weather resistance and fire protection bonding in electric vehicle battery packs, especially in high temperature and high humidity environments, and commonly used thermally conductive adhesives are difficult to maintain structural performance when the filling amount increases.

Method used

A two-component fire protection polyurethane glue is used to mix the polyurethane prepolymer containing aluminum hydroxide with components such as catalysts and polyols to form an adhesive with a high fill amount, which has excellent thermal conductivity and structural strength.

Benefits of technology

It realizes high-strength bonding in electric vehicle battery packs, has V0 fire protection, and maintains excellent bonding performance under long-term high temperature and high humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510408000001
    Figure 2025510408000001
  • Figure 2025510408000002
    Figure 2025510408000002
  • Figure 2025510408000003
    Figure 2025510408000003
Patent Text Reader

Abstract

Provided herein is a two-part thermally conductive, flame retardant polyurethane adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of adhesives, in particular two-part polyurethane adhesives. [Background technology]

[0002] The continued drive for lightweighting has led to an increased use of aluminum alloys in building blocks for vehicle body design. Especially in electric vehicles (EVs), batteries add to the overall vehicle weight. The battery itself uses many aluminum alloys for various structures and components. For example, the housing of the battery pack is typically made of aluminum, and the side and edge panels of the battery module are also made of aluminum alloys. The joining of aluminum alloys to other components of the battery becomes critical. Adhesive joining is currently a common joining method for aluminum in the automotive industry, along with other joining methods such as welding and riveting. Typical joint strengths required for joining structural components need to be greater than 5 MPa, or preferably 10 MPa or higher.

[0003] The most commonly used adhesives for joining aluminum alloys are based on epoxy and acrylic chemistries. However, epoxy adhesives have a relatively slow cure rate and can be brittle in the cured state. This precludes the use of epoxy-based adhesives for structural joining of aluminum alloys within battery pack applications. Acrylic-based adhesives often have an unpleasant odor and are not very user-friendly.

[0004] Polyurethane (PU)-based adhesives are typically used to bond painted substrates and plastic-based components in automotive applications. However, PU-based adhesives typically do not provide strong and durable bonds to aluminum alloys, and adhesion, especially to aluminum, is significantly reduced when exposed to harsh weathering conditions such as high temperature and high humidity. In addition, in battery applications, adhesives used inside the battery pack must be fire or flame resistant. Flame retardant additives typically used in the polyurethane industry are halogen-containing or phosphorus-based. Unfortunately, these additives often dramatically reduce the adhesive or bonding performance of the adhesive, thereby compromising the structural properties of the bonded system.

[0005] There is an increasing trend in the industry to bond battery cells with thermally conductive adhesives that have dual functions to provide not only thermal conductivity but also structural bonding. Thermally conductive adhesives usually require high loadings of thermally conductive fillers (>50 wt%) to achieve thermal conductivity above 1 W / mK, which makes it difficult to maintain the structural properties, especially the bond strength to aluminum, especially after aging. Summary of the Invention [Means for solving the problem]

[0006] In a first aspect, the present invention provides a method for producing a composition comprising the steps of: (A) (a1) a polyurethane prepolymer prepared from at least one polyol, at least one polyisocyanate, and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; A first liquid containing (B) (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); A second liquid containing A two-part flame retardant polyurethane adhesive formulation comprising: Part A and / or Part B contain aluminum hydroxide such that when Part A and Part B are mixed together to form the adhesive mixture (preferably in a 1:1 volume ratio), the aluminum hydroxide concentration is at least 50% by weight; A two-part flame retardant polyurethane adhesive formulation is provided.

[0007] 1. A method for bonding two or more substrates, comprising the steps of: (1) (A) (a1) a polyurethane prepolymer prepared from at least one polyol, at least one polyisocyanate, and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; A first liquid containing (B) (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); A second liquid containing providing a two-part flame retardant polyurethane adhesive formulation comprising: Part A and / or Part B contain aluminum hydroxide such that when Part A and Part B are mixed together to form the adhesive mixture (preferably in a 1:1 volume ratio) there is an aluminum hydroxide concentration of at least 50% by weight; (2) Mixing parts A and B to obtain an uncured adhesive; (3) applying the uncured adhesive to at least one substrate; (4) bringing the uncured adhesive into adhesive contact with a second substrate; (5) curing the uncured adhesive; The method includes:

[0008] (1) a first substrate; (2) a second substrate; A bonded assembly comprising: a first substrate and a second substrate bonded together by a cured adhesive obtained by mixing together parts A and B; Liquid A is (A) (a1) a polyurethane prepolymer prepared from at least one polyol, at least one polyisocyanate, and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; The first liquid comprises Liquid B is (B) (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); A second liquid comprising: A bonded assembly, wherein parts A and / or B contain aluminum hydroxide such that when parts A and B are mixed together to form an adhesive mixture (preferably a 1:1 volume ratio), the aluminum hydroxide concentration is at least 50% by weight, and the mixture is allowed to cure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The inventors have discovered that by formulating a thermally conductive flame retardant adhesive with a polyurethane, it is possible to obtain i) a lap shear strength of greater than 7.5 MPa against aluminum, ii) a flame retardant rating of V0, and iii) excellent retention of lap shear strength after extended exposure to harsh conditions.

[0010] Definitions and Abbreviations DSC Differential Scanning Calorimetry MDI 4,4'-methylenebis(phenylisocyanate) HDI Hexamethylene Diisocyanate IPDI Isophorone Diisocyanate PU Polyurethane SEC Size Exclusion Chromatography RH Relative Humidity ATH Aluminum trihydroxide, aluminum hydroxide

[0011] The equivalent weight and molecular weight were determined by gel permeation chromatography (GPC) using a Malvern Viscothek GPC max instrument, with tetrahydrofuran (THF) as the eluent, PL GEL MIXED D (Agilent, 300*7.5mm, 5μm) as the column, and MALVERN Viscotek TDA (integrated refractive index viscometer and light scattering) as the detector.

[0012] The adhesive of the present invention is a two-part polyurethane adhesive comprising parts A and B. Parts A and B can be packaged together as a kit. Parts A and B are mixed together in the appropriate ratio, preferably a 1:1 volume ratio, prior to use, and then applied to one or more substrates as soon as possible.

[0013] Liquids A and B are disclosed in further detail below.

[0014] Liquid A (isocyanate) Part A comprises a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate, and an aminosilane, the prepolymer being partially terminated with silane moieties and having reactive NCO sites.

[0015] The polyisocyanate used to prepare the prepolymer may be aliphatic, aromatic, or mixed, with aromatic polyisocyanates being preferred. Examples of aromatic polyisocyanates include methylene diphenyl diisocyanate (MDI), polycarbodiimide-modified MDI, toluene diisocyanate (TDI), p-phenylene diisocyanate (PPDI), and naphthalene diisocyanate (NDI). MDI and / or polycarbodiimide-modified MDI are particularly preferred. In some embodiments, a mixture of MDI and polycarbodiimide-modified MDI is used.

[0016] The polyisocyanate used in the production of the prepolymer is preferably used in an amount of 15 to 40% by weight, more preferably 17 to 35% by weight, and particularly preferably 20 to 32% by weight, based on the total weight of component A.

[0017] In a particularly preferred embodiment, the prepolymer is produced using 15 to 40% by weight, more preferably 17 to 35% by weight, and especially preferably 20 to 32% by weight, of MDI and / or polycarbodiimide-modified MDI, based on the total weight of component A.

[0018] The polyol used in the preparation of the prepolymer is preferably a polyether polyol. The polyol may have two or more OH groups. Examples of polyether polyols include poly(alkylene oxide) diols, in which the alkylene groups are C2-C6, particularly preferably the alkylene groups are C2-C4. Examples of suitable polyols include poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols. Poly(propylene oxide) polyols, in particular poly(propylene glycol), are particularly preferred. In a preferred embodiment, the polyether polyol is a polyether polyol based on propylene glycol. In a particularly preferred embodiment, it is a polyether polyol based on propylene glycol capped with ethylene oxide, having a molecular weight of about 2,000 Da and a functionality of 2.

[0019] The polyether polyol used in the production of the prepolymer is preferably used in an amount of 5 to 20% by weight, more preferably 8 to 15% by weight, and particularly preferably 9 to 12% by weight, based on the total weight of component A.

[0020] In a preferred embodiment, the polyol used to prepare the prepolymer is a polyether polyol based on propylene glycol and is used in an amount of 5 to 20% by weight, more preferably 8 to 15% by weight, and particularly preferably 9 to 12% by weight, based on the total weight of component A.

[0021] The polyisocyanate is used in excess relative to the polyether polyol so that the prepolymer is terminated with isocyanate groups. The final prepolymer preferably has an NCO weight percent in the range of 5-30 wt.%, more preferably in the range of 10-25 wt.%.

[0022] The aminosilane in component A preferably has the general formula I or the general formula II:

[0023] [ka]

[0024] (In the formula, R 1 are independently selected from C1 to C6 alkyl; R 2 are independently selected from C2 to C6 alkylene.

[0025] In a preferred embodiment, the aminosilane of component A is of general formula I, R 1 is a C1-C2 alkyl and R2 is a C2-C4 alkylene. In a more preferred embodiment, the aminosilane is of general formula I, where R 1 is methyl and R2 is propylene.

[0026] In another preferred embodiment, the aminosilane in component A is of the general formula II, R 1 is a C1-C2 alkyl and R2 is a C2-C4 alkylene. In a more preferred embodiment, the aminosilane is of general formula II, where R 1 is methyl and R2 is propylene.

[0027] In a particularly preferred embodiment, the aminosilane in component A is bis(trimethoxysilylpropyl)amine.

[0028] The aminosilane in component A is preferably used in an amount of 0.5 to 4% by weight, more preferably 1 to 3% by weight, and particularly preferably 1.5 to 2.5% by weight, based on the total weight of component A.

[0029] In a preferred embodiment, the aminosilane in Component A is bis(trimethoxysilylpropyl)amine, which is used in an amount of 0.5 to 4% by weight, more preferably 1 to 3% by weight, and particularly preferably 1.5 to 2.5% by weight, based on the total weight of Component A.

[0030] In a preferred embodiment, the prepolymer in component A is made using: 15 to 40% by weight, more preferably 17 to 35% by weight, particularly preferably 20 to 32% by weight, of polyisocyanate, based on the total weight of component A; from 5 to 20% by weight, more preferably from 8 to 15% by weight, particularly preferably from 9 to 12% by weight, of polyether polyol, based on the total weight of component A; and 0.5 to 4% by weight, more preferably 1 to 3% by weight, particularly preferably 1.5 to 2.5% by weight, of aminosilane, based on the total weight of component A.

[0031] In a more preferred embodiment, the prepolymer in component A is made using: 15 to 40% by weight, more preferably 17 to 35% by weight, particularly preferably 20 to 32% by weight, of MDI and / or polycarbodiimide-modified MDI or a mixture of MDI and polycarbodiimide-modified MDI, based on the total weight of component A; from 5 to 20% by weight, more preferably from 8 to 15% by weight and particularly preferably from 9 to 12% by weight, based on the total weight of component A, of a polyether polyol based on propylene glycol, preferably a polyether polyol based on propylene glycol having an OH number (mg KOH / g) of 109 to 115; From 0.5 to 4% by weight, more preferably from 1 to 3% by weight, particularly preferably from 1.5 to 2.5% by weight, based on the total weight of component A, of aminosilanes of the general formula II (where R 1 is C1-C2 alkyl, R2 is C2-C4 alkylene, more preferably R 1 is methyl and R2 is propylene).

[0032] In a particularly preferred embodiment, the prepolymer in component A is prepared using: 20-32% by weight, based on the total weight of component A, of a mixture of MDI and polycarbodiimide-modified MDI; 9 to 12% by weight, based on the total weight of component A, of a polyether polyol based on propylene glycol having an OH number (mg KOH / g) of 109 to 115; and · 0.5 to 4 wt. %, more preferably 1 to 3 wt. %, and particularly preferably 1.5 to 2.5 wt. % of bis-(trimethoxysilylpropyl)amine, based on the total weight of component A.

[0033] The prepolymer is prepared by mixing the components, preferably in a dry and / or inert atmosphere, for a time sufficient for substantially all of the OH groups of the polyol and the amino groups of the aminosilane to react with the polyisocyanate. In a preferred embodiment, mixing is carried out for 1 to 2 hours. The ratios are selected so that the prepolymer is terminated with isocyanate groups and partially with silane groups.

[0034] B liquid (polyol) Liquid B is one or more polyether polyols; and one or more catalysts capable of promoting the reaction of the NCO sites of the prepolymer with the polyol of component B; Includes.

[0035] The polyol used in component B is a polyether polyol. The polyol may have two or more OH groups. Examples of polyether polyols include poly(alkylene oxide) diols, in which the alkylene groups are C2 to C6, particularly preferably the alkylene groups are C2 to C4. Examples of suitable polyols include poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols. Poly(propylene oxide) polyols are particularly preferred.

[0036] In a preferred embodiment, the polyether polyol of component B is a diol.

[0037] In another preferred embodiment, the polyether polyol of component B is a mixture of polyols having a functionality of 2 to 6. In a particularly preferred embodiment, the polyether polyol of component B is a mixture of at least one diol, at least one triol and at least one polyol having a functionality greater than 3.

[0038] In a preferred embodiment, the polyether polyol of Component B is a mixture comprising or consisting of diols, triols and polyols having a nominal functionality of 5-6.

[0039] In a preferred embodiment, the polyether polyol of Component B is a poly(propylene oxide) polyol having a functionality of two.

[0040] In a preferred embodiment, the polyether polyol of component B is a mixture of poly(propylene oxide) polyols having a functionality of 2 to 6. In a particularly preferred embodiment, the polyether polyol of component B is a mixture comprising or consisting of at least one poly(propylene oxide) diol, at least one poly(propylene oxide) triol, and at least one poly(propylene oxide) polyol of functionality greater than 3.

[0041] In a preferred embodiment, the polyether polyol of Component B is a mixture comprising or consisting of poly(propylene oxide) diols, poly(propylene oxide) triols, and poly(propylene oxide) polyols having a nominal functionality of 5 to 6.

[0042] In another preferred embodiment, the polyether polyol of Component B consists of a poly(propylene oxide) diol.

[0043] In another preferred embodiment, the polyether polyol of Component B comprises, based on the total weight of the polyether polyols in Component B, 0 to 45 wt. % of a polyether triol, 0 to 30 wt. % of a polyether polyol having a functionality greater than 3, and 25 to 100 wt. % of a polyether diol.

[0044] In another preferred embodiment, the polyether polyol of component B comprises, based on the total weight of the polyether polyols in component B, 5 to 45 wt. % of a polyether triol, 10 to 35 wt. % of a polyether polyol having a functionality greater than 3, and 30 to 80 wt. % of a polyether diol.

[0045] In another preferred embodiment, the polyether polyol of Component B comprises, based on the total weight of the polyether polyols in Component B, 0 to 45 wt. % of a poly(propylene oxide) triol, 0 to 30 wt. % of a poly(propylene oxide) polyol having a functionality greater than 3, and 25 to 100 wt. % of a poly(propylene oxide) diol.

[0046] The combined polyether polyols in Component B are preferably present in an amount of from 15 to 50% by weight, more preferably from 16 to 45% by weight, and especially preferably from 18 to 42% by weight, based on the total weight of Component B.

[0047] In a preferred embodiment, component B comprises from 15 to 50% by weight, more preferably from 16 to 45% by weight, particularly preferably from 18 to 42% by weight, based on the total weight of component B, of a mixture of polyether polyols which comprises or consists of: (1) 30 to 45 weight percent of a polyether triol, 19 to 30 weight percent of a polyether polyol having a functionality greater than 3, and 27 to 40 weight percent of a polyether diol, based on the total weight of the polyether polyols in component B; or (2) 5 to 15 weight percent of a polyether triol, 10 to 25 weight percent of a polyether polyol having a functionality greater than 3, and 70 to 80 weight percent of a polyether diol, based on the total weight of the polyether polyols in component B; or (3) 100% by weight of a polyether diol, based on the total weight of the polyether polyols in component B; or (4) 30 to 45 weight percent of a poly(propylene oxide) triol, 19 to 30 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 27 to 40 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols in component B; or (5) 5 to 15 weight percent of a poly(propylene oxide) triol, 10 to 25 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 70 to 80 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols in component B.

[0048] Component B may optionally include diols and / or triols with a molecular weight of less than 200 Da, more preferably less than 150 Da. Examples of diols include propylene glycol and butanediol, with butanediol (e.g., 1,4-butanediol) being particularly preferred. Examples of triols include glycerin and trimethylolpropane, with glycerin being particularly preferred.

[0049] When present, diols or triols having a molecular weight of less than 200 Da are preferably used at 2 to 8 wt. %, more preferably 2.5 to 5 wt. %, based on the total weight of component B.

[0050] In a preferred embodiment, Component B comprises 2 to 8 wt. %, more preferably 2.5 to 5 wt. %, of butanediol (eg, 1,4-butanediol), based on the total weight of Component B.

[0051] In another preferred embodiment, Component B comprises 2 to 8 wt. %, more preferably 2.5 to 5 wt. %, of glycerin, based on the total weight of Component B.

[0052] Component B comprises one or more catalysts capable of promoting the reaction of the NCO sites of the prepolymer of Component A with one or more polyether polyols of Component B.

[0053] The catalyst is preferably selected from Lewis bases and Lewis acids, preferably tertiary amines such as diazabicyclo[2.2.2]octane, tris-2,4,6-((dimethylamino)methyl)phenol, DMDEE (2,2'-dimorpholinodiethyl ether), imidazole (e.g. 4-methylimidazole), triethanolamine, polyethyleneimine, and especially diazabicyclo[2.2.2]octane.

[0054] Also suitable are organotin compounds such as dioctyltin dineodecanoate, dibutyltin di(acetate), and di-n-octyltin bis(isooctylmercaptoacetate). Di-n-octyltin bis(isooctylmercaptoacetate) is particularly preferred.

[0055] The catalyst is preferably used in an amount of 0.005 to 0.02% by weight, more preferably 0.0075 to 0.015% by weight, and particularly preferably 0.01% by weight, based on the total weight of component B.

[0056] In a preferred embodiment, the catalyst is di-n-octyltin bis(isooctylmercaptoacetate) and is used in an amount of 0.005 to 0.02% by weight, more preferably 0.0075 to 0.015% by weight, and particularly preferably 0.01% by weight, based on the total weight of component B.

[0057] Aluminum hydroxide Part A and / or Part B contain aluminum hydroxide, and when Parts A and B are mixed together to form an adhesive mixture (preferably in a 1:1 volume ratio), the aluminum hydroxide concentration is at least 50 wt. % based on the total weight of the adhesive mixture.

[0058] Preferably, the aluminum hydroxide concentration in the adhesive mixture is from 50 to 70% by weight, more preferably from 55 to 68% by weight, based on the total weight of the mixture.

[0059] In a preferred embodiment, aluminum hydroxide is present in Component A at 50 to 70% by weight, more preferably 55 to 68% by weight, based on the total weight of Component A.

[0060] In another preferred embodiment, aluminum hydroxide is present in Component B at 50 to 70 wt. %, more preferably 55 to 68 wt. %, based on the total weight of Component B.

[0061] In a preferred embodiment, aluminum hydroxide is present in both component A and component B.

[0062] In another preferred embodiment, aluminum hydroxide is present in both component A and component B in an amount of 50 to 70% by weight, more preferably 55 to 68% by weight, based on the total weight of each component.

[0063] In a preferred embodiment, the aluminum hydroxide has a D of about 20 microns. 50 has.

[0064] Preferably, the adhesive mixture obtained by mixing component A with component B (preferably in a 1:1 volume ratio) has a D of about 20 microns. 50 The mixture contains 50 to 70% by weight, more preferably 55 to 68% by weight, of aluminum hydroxide having the formula given above based on the total weight of the mixture.

[0065] In another preferred embodiment, component A has a D 50The aluminum hydroxide having the formula: is contained in an amount of 50 to 70% by weight, more preferably 55 to 68% by weight, based on the total weight of component A.

[0066] In another preferred embodiment, component B has a D of about 20 microns. 50 The aluminum hydroxide having the formula: is contained in an amount of 50 to 70% by weight, more preferably 55 to 68% by weight, based on the total weight of component B.

[0067] In another preferred embodiment, both component A and component B have a D 50 The aluminum hydroxide having the formula (I) is contained in an amount of 50 to 70% by weight, more preferably 55 to 68% by weight, based on the total weight of each component.

[0068] Optional ingredients for components A and B Components A and / or B may additionally contain other materials such as, for example, talc, molecular sieves, silica (especially amorphous silica), carbon black, and the like.

[0069] Application to substrate Parts (A) and (B) can be mixed and applied to a substrate using known methods such as a manual application system or an automated method using a pump system using a 20 liter pail or a 200 liter drum or any other suitable container.

[0070] Preferred substrates include aluminum, electrocoated aluminum, electrocoated steel, laser treated aluminum, or passivated aluminum.

[0071] Features The cured adhesive composition obtained by mixing components A and B preferably has a thermal conductivity of at least 0.75 W / mK, more preferably at least 0.8 W / mK, when measured according to ASTM D5470, after curing and standing for 7 days at 23° C. and 50% relative humidity.

[0072] The cured adhesive composition obtained by mixing components A and B preferably has a lap shear strength on an aluminum substrate of 7.5 MPa or greater, more preferably 8 MPa or greater, after curing and standing for 7 days at 23°C and 50% relative humidity, when measured according to the method set forth in the Examples.

[0073] The cured adhesive composition obtained by mixing components A and B preferably has a lap shear strength on an aluminum substrate of at least 6 MPa, more preferably at least 8 MPa, and especially preferably at least 9 MPa, when measured according to the method shown in the examples, after curing and standing for 7 days at 23°C and 50% relative humidity, followed by cataplasma treatment for 7 days.

[0074] The cured adhesive composition obtained by mixing components A and B preferably has a lap shear strength on an aluminum substrate of 8 MPa or greater, more preferably 9 MPa or greater, after curing and storing for 7 days at 23° C. and 50% relative humidity followed by storing for 168 hours at 85° C. and 85% relative humidity, when measured according to the method set forth in the Examples.

[0075] The cured adhesive composition obtained by mixing components A and B preferably has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPa or more, after curing and standing for 7 days at 23°C and 50% relative humidity followed by standing for 1,000 hours at 85°C and 85% relative humidity, when measured according to the method shown in the examples.

[0076] The cured adhesive composition obtained by mixing components A and B preferably has a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0077] In a preferred embodiment, the cured adhesive composition obtained by mixing components A and B (7 days at 23° C. and 50% relative humidity) has a lap shear strength on an aluminum substrate of at least 7.5 MPa, more preferably at least 8 MPa, after curing for 7 days at 23° C. and 50% relative humidity and standing, when measured according to the method set forth in the examples, and has a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0078] In another preferred embodiment, the cured adhesive (7 days at 23°C and 50% relative humidity) has a lap shear strength on an aluminum substrate after 7 days of Cataplasma treatment of 6 MPa or more, more preferably 8 MPa or more, and especially preferably 9 MPa or more, when measured according to the method shown in the examples, and has a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

[0079] In another preferred embodiment, the cured adhesive (7 days at 23° C. and 50% relative humidity) has a lap shear strength of 8 MPa or greater, more preferably 9 MPa or greater, on an aluminum substrate after 168 hours at 85° C. and 85% relative humidity, as measured according to the method set forth in the Examples, and has a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0080] In another preferred embodiment, the cured adhesive composition obtained by mixing components A and B (7 days at 23°C and 50% relative humidity) has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPa or more, after 1,000 hours at 85°C and 85% relative humidity, when measured according to the method shown in the examples, and has a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

[0081] In another preferred embodiment, the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 7.5 MPa or greater, more preferably 8 MPa or greater, after curing and standing for 7 days at 23° C. and 50% relative humidity, when measured according to the method shown in the examples, and a thermal conductivity of 0.75 W / mK or greater, more preferably 0.8 W / mK or greater, when measured according to ASTM D5470.

[0082] In another preferred embodiment, the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of at least 6 MPa, more preferably at least 8 MPa, and especially preferably at least 9 MPa, after curing and standing for 7 days at 23°C and 50% relative humidity followed by cataplasma treatment for 7 days, when measured according to the method shown in the examples, and a thermal conductivity of at least 0.75 W / mK, more preferably at least 0.8 W / mK, when measured according to ASTM D5470.

[0083] In another preferred embodiment, the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 8 MPa or greater, more preferably 9 MPa or greater, after curing and storing for 7 days at 23° C. and 50% relative humidity followed by storing for 168 hours at 85° C. and 85% relative humidity, when measured according to the method shown in the examples, and a thermal conductivity of 0.75 W / mK or greater, more preferably 0.8 W / mK or greater, when measured according to ASTM D5470.

[0084] In another preferred embodiment, the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of at least 8 MPa, more preferably at least 9 MPa, and especially preferably at least 10 MPa, after curing and storing for 7 days at 23° C. and 50% relative humidity followed by storing for 1,000 hours at 85° C. and 85% relative humidity, when measured according to the method shown in the examples, and a thermal conductivity of at least 0.75 W / mK, more preferably at least 0.8 W / mK, when measured according to ASTM D5470.

[0085] Particularly preferred embodiments The following are particularly preferred embodiments of the present invention: 1. (A) (a1) a polyurethane prepolymer prepared from at least one polyol, at least one polyisocyanate, and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; A first liquid containing (B) (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); A second liquid containing A two-part flame retardant polyurethane adhesive formulation comprising: Part A and / or Part B contain aluminum hydroxide such that when Part A and Part B are mixed together to form the adhesive mixture (preferably in a 1:1 volume ratio), the aluminum hydroxide concentration is at least 50% by weight; A two-part flame retardant polyurethane adhesive formulation. 2. A method for bonding two or more substrates, comprising the steps of: (1) (A) (a1) a polyurethane prepolymer prepared from at least one polyol, at least one polyisocyanate, and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; A first liquid containing (B) (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); A second liquid containing providing a two-part flame retardant polyurethane adhesive formulation comprising: Part A and / or Part B contain aluminum hydroxide such that when Part A and Part B are mixed together to form the adhesive mixture (preferably in a 1:1 volume ratio) there is an aluminum hydroxide concentration of at least 50% by weight; (2) Mixing parts A and B to obtain an uncured adhesive; (3) applying the uncured adhesive to at least one substrate; (4) bringing the uncured adhesive into adhesive contact with a second substrate; (5) curing the uncured adhesive; The method includes: 3. (1) a first substrate; (2) a second substrate; A bonded assembly comprising: a first substrate and a second substrate bonded together by a cured adhesive obtained by mixing together parts A and B of: Liquid A is (A) (a1) a polyurethane prepolymer prepared from at least one polyol, at least one polyisocyanate, and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; a first liquid comprising: Liquid B is (B) (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); a second liquid comprising: A bonded assembly, wherein parts A and / or B contain aluminum hydroxide such that when parts A and B are mixed together to form an adhesive mixture (preferably a 1:1 volume ratio), the aluminum hydroxide concentration is at least 50% by weight, and the mixture is allowed to cure. 4. Any one of the preceding embodiments, wherein the polyisocyanate used to make the prepolymer is selected from aliphatic polyisocyanates, aromatic polyisocyanates, and mixtures thereof. 5. Any one of the preceding embodiments, wherein the polyisocyanate used to make the prepolymer is selected from aromatic polyisocyanates. 6. Any one of the preceding embodiments, wherein the polyisocyanate used to make the prepolymer is selected from methylene diphenyl diisocyanate (MDI), polycarbodiimide modified MDI, toluene diisocyanate (TDI), p-phenylene diisocyanate (PPDI), and naphthalene diisocyanate (NDI). 7. Any one of the preceding embodiments, wherein the polyisocyanate used to make the prepolymer is MDI and / or polycarbodiimide modified MDI. 8. Any one of the preceding embodiments, wherein the polyisocyanate used to prepare the prepolymer is used in an amount of 15 to 40% by weight, more preferably 17 to 35% by weight, and particularly preferably 20 to 32% by weight, based on the total weight of component A. 9. Any one of the preceding embodiments, wherein the prepolymer is made using 15 to 40 wt. %, more preferably 17 to 35 wt. %, and particularly preferably 20 to 32 wt. % MDI and / or polycarbodiimide-modified MDI, based on the total weight of component A. 10. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer is a polyether polyol. 11. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer comprises a polyol selected from poly(alkylene oxide) diols, wherein the alkylene groups are C2-C6, and particularly preferably the alkylene groups are C2-C4, and mixtures thereof. 12. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer comprises a polyol selected from poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols, and mixtures thereof. 13. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer comprises a polyol selected from poly(propylene oxide) polyols. 14. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer comprises an ethylene oxide-capped propylene glycol-based polyether polyol having a molecular weight of about 2,000 Da and a functionality of 2. 15. Any one of the preceding embodiments, wherein the polyether polyol used to prepare the prepolymer is used in an amount of 5 to 20 wt. %, more preferably 8 to 15 wt. %, and particularly preferably 9 to 12 wt. %, based on the total weight of component A. 16. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer is a polyether polyol based on propylene glycol and is used at 5 to 20 wt. %, more preferably 8 to 15 wt. %, and especially preferably 9 to 12 wt. %, based on the total weight of component A. 17. Any one of the preceding embodiments, wherein the final prepolymer has an NCO wt% in the range of 5 to 30 wt%, more preferably 10 to 25 wt%. 18. Any one of the preceding embodiments, wherein the aminosilane in component A preferably has general formula I or general formula II:

[0086] [ka]

[0087] (In the formula, R 1 are independently selected from C1 to C6 alkyl; R 2 are independently selected from C2 to C6 alkylene. 19. The aminosilane in component A is of general formula I, R 1 Any one of the preceding embodiments, wherein R is C1-C2 alkyl and R is C2-C4 alkylene. In a more preferred embodiment, the aminosilane is of general formula I, where R 1 is methyl and R2 is propylene. 20. The aminosilane in component A is of general formula II, R 1 Any one of the preceding embodiments, wherein R is C1-C2 alkyl and R is C2-C4 alkylene. 21. The aminosilane is of general formula II, R 1 Any one of the preceding embodiments, wherein R is methyl and R2 is propylene. 22. Any one of the preceding embodiments, wherein the aminosilane of component A is bis(trimethoxysilylpropyl)amine. 23. Any one of the preceding embodiments, wherein the aminosilane in component A is preferably used in an amount of 0.5 to 4 wt.%, more preferably 1 to 3 wt.%, and particularly preferably 1.5 to 2.5 wt.%, based on the total weight of component A. 24. Any one of the preceding embodiments, wherein the aminosilane in component A is bis(trimethoxysilylpropyl)amine and is used at 0.5 to 4 wt. %, more preferably 1 to 3 wt. %, and particularly preferably 1.5 to 2.5 wt. %, based on the total weight of component A. 25. The prepolymer in component A is 15 to 40% by weight, more preferably 17 to 35% by weight, particularly preferably 20 to 32% by weight, of polyisocyanate, based on the total weight of component A; from 5 to 20% by weight, more preferably from 8 to 15% by weight, particularly preferably from 9 to 12% by weight, of polyether polyol, based on the total weight of component A; and 0.5 to 4% by weight, more preferably 1 to 3% by weight, particularly preferably 1.5 to 2.5% by weight, of aminosilane, based on the total weight of component A; Any one of the preceding embodiments, wherein the fluororesin is fabricated using 26. The prepolymer in component A is 15 to 40% by weight, more preferably 17 to 35% by weight, particularly preferably 20 to 32% by weight, of MDI and / or polycarbodiimide-modified MDI or a mixture of MDI and polycarbodiimide-modified MDI, based on the total weight of component A; from 5 to 20% by weight, more preferably from 8 to 15% by weight and particularly preferably from 9 to 12% by weight, based on the total weight of component A, of a polyether polyol based on propylene glycol, preferably a polyether polyol based on propylene glycol having an OH number (mg KOH / g) of 109 to 115; From 0.5 to 4% by weight, more preferably from 1 to 3% by weight, particularly preferably from 1.5 to 2.5% by weight, based on the total weight of component A, of aminosilanes of the general formula II (where R 1 is C1-C2 alkyl, R2 is C2-C4 alkylene, more preferably R 1 is methyl and R2 is propylene) Any one of the preceding embodiments, wherein the fluororesin is fabricated using 27. The prepolymer in component A is 20-32% by weight, based on the total weight of component A, of a mixture of MDI and polycarbodiimide-modified MDI; 9 to 12% by weight, based on the total weight of component A, of a polyether polyol based on propylene glycol having an OH number (mg KOH / g) of 109 to 115; and 0.5 to 4% by weight, more preferably 1 to 3% by weight, and particularly preferably 1.5 to 2.5% by weight, of bis-(trimethoxysilylpropyl)amine, based on the total weight of component A Any one of the preceding embodiments, wherein the fluororesin is fabricated using 28. Any one of the preceding embodiments, wherein the polyol used in component B is a polyether polyol. 29. Any one of the preceding embodiments, wherein the polyol used in component B has two or more OH groups. 30. Any one of the preceding embodiments, wherein the polyol used in component B is selected from poly(alkylene oxide) diols, wherein the alkylene groups are C2-C6, and particularly preferably the alkylene groups are C2-C4. 31. Any one of the preceding embodiments, wherein the polyol used in component B is selected from poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols. 32. Any one of the preceding embodiments, wherein the polyol used in component B is selected from poly(propylene oxide) polyols. 33. Any one of the preceding embodiments, wherein the polyol used in component B comprises a polyol selected from polyether diols. 34. Any one of the preceding embodiments, wherein the polyether polyol of component B is a mixture of polyols having a functionality of 2-6. 35. Any one of the preceding embodiments, wherein the polyether polyol of component B is a mixture of at least one diol, at least one triol, and at least one polyol of functionality greater than 3. 36. Any one of the preceding embodiments, wherein the polyether polyol of component B is a mixture comprising or consisting of diols, triols, and polyols having a nominal functionality of 5 to 6. 37. Any one of the preceding embodiments, wherein the polyether polyol of component B comprises a poly(propylene oxide) polyol having a functionality of 2. 38. Any one of the preceding embodiments, wherein the polyether polyol of component B is a mixture of poly(propylene oxide) polyols having a functionality from 2 to 6. 39. Any one of the preceding embodiments wherein the polyether polyol of component B is a mixture comprising or consisting of at least one poly(propylene oxide) diol, at least one poly(propylene oxide) triol, and at least one poly(propylene oxide) polyol of functionality greater than 3. 40. Any one of the preceding embodiments, wherein the polyether polyol of component B is a mixture comprising or consisting of a poly(propylene oxide) diol, a poly(propylene oxide) triol, and a poly(propylene oxide) polyol having a nominal functionality of 5 to 6. 41. Any one of the preceding embodiments, wherein the polyether polyol of Component B comprises, based on the total weight of the polyether polyols in Component B, 0 to 45 wt. % of a polyether triol, 0 to 30 wt. % of a polyether polyol having a functionality greater than 3, and 25 to 100 wt. % of a polyether diol. 42. Any one of the preceding embodiments, wherein the polyether polyol of Component B comprises 5 to 45 wt. % of a polyether triol, 10 to 35 wt. % of a polyether polyol having a functionality greater than 3, and 30 to 80 wt. % of a polyether diol, based on the total weight of the polyether polyols in Component B. 43. Any one of the preceding embodiments, wherein the polyether polyol of Component B comprises, based on the total weight of the polyether polyols in Component B, 0 to 45 wt. % of a poly(propylene oxide) triol, 0 to 30 wt. % of a poly(propylene oxide) polyol having a functionality greater than 3, and 25 to 100 wt. % of a poly(propylene oxide) diol. 44. Any one of the preceding embodiments, wherein the combined polyether polyols in Component B are present in an amount from 15 to 50 weight percent, more preferably from 16 to 45 weight percent, and particularly preferably from 18 to 42 weight percent, based on the total weight of Component B. 45. Any one of the preceding embodiments, wherein component B comprises 15 to 50 wt. %, more preferably 16 to 45 wt. %, and particularly preferably 18 to 42 wt. %, based on the total weight of component B, of a mixture of polyether polyols comprising or consisting of: (1) 30 to 45 weight percent of a polyether triol, 19 to 30 weight percent of a polyether polyol having a functionality greater than 3, and 27 to 40 weight percent of a polyether diol, based on the total weight of the polyether polyols in component B; or (2) 5 to 15 weight percent of a polyether triol, 10 to 25 weight percent of a polyether polyol having a functionality greater than 3, and 70 to 80 weight percent of a polyether diol, based on the total weight of the polyether polyols in component B; or (3) 100% by weight of a polyether diol, based on the total weight of the polyether polyols in component B; or (4) 30 to 45 weight percent of a poly(propylene oxide) triol, 19 to 30 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 27 to 40 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols in component B; or (5) 5 to 15 weight percent of a poly(propylene oxide) triol, 10 to 25 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 70 to 80 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols in component B. 46. ​​Any one of the preceding embodiments, wherein component B comprises a diol and / or triol with a molecular weight of less than 200 Da, more preferably less than 150 Da. 47. Any one of the preceding embodiments, wherein component B comprises a butanediol (e.g., 1,4-butanediol). 48. Any one of the preceding embodiments, wherein component B comprises glycerin. 49. Any one of the preceding embodiments, wherein component B comprises 2 to 8 wt. %, more preferably 2.5 to 5 wt. %, of a diol or triol having a molecular weight of less than 200 Da, based on the total weight of component B. 50. Any one of the preceding embodiments, wherein component B comprises butanediol (e.g., 1,4-butanediol) in an amount of 2 to 8 wt.%, more preferably 2.5 to 5 wt.%, based on the total weight of component B. 51. Any one of the preceding embodiments, wherein component B comprises glycerin in an amount of 2-8% by weight, more preferably 2.5-5% by weight, based on the total weight of component B. 52. Any one of the preceding embodiments, wherein the catalyst is selected from a Lewis base and a Lewis acid. 53. Any one of the preceding embodiments, wherein the catalyst is selected from a tertiary amine, an organotin compound, and combinations thereof. 54. Any one of the preceding embodiments, wherein the catalyst comprises diazabicyclo[2.2.2]octane. 55. Any one of the preceding embodiments, wherein the catalyst comprises an organotin compound. 56. Any one of the preceding embodiments, wherein the catalyst comprises di-n-octyltin bis(isooctylmercaptoacetate). 57. Any one of the preceding embodiments, wherein the catalyst is used in an amount of 0.005 to 0.02 wt. %, more preferably 0.0075 to 0.015 wt. %, and particularly preferably 0.01 wt. %, based on the total weight of component B. 58. Any one of the preceding embodiments, wherein the catalyst is di-n-octyltin bis(isooctylmercaptoacetate) and is used at 0.005 to 0.02 wt %, more preferably 0.0075 to 0.015 wt %, and particularly preferably 0.01 wt %, based on the total weight of component B. 59. Any one of the preceding embodiments, wherein the aluminum hydroxide concentration in the adhesive mixture obtained by mixing components A and B is 50-70% by weight, more preferably 55-68% by weight, based on the total weight of the mixture. 60. Any one of the preceding embodiments, wherein the aluminum hydroxide is present in Component A at 50-70% by weight, more preferably 55-68% by weight, based on the total weight of Component A. 61. Any one of the preceding embodiments, wherein the aluminum hydroxide is present in Component B at 50-70% by weight, more preferably 55-68% by weight, based on the total weight of Component B. 62. Any one of the preceding embodiments, wherein aluminum hydroxide is present in both component A and component B. 63. Any one of the preceding embodiments, wherein aluminum hydroxide is present in both component A and component B at 50-70% by weight, more preferably 55-68% by weight, based on the total weight of each component. 64. Aluminum hydroxide is about 20 microns in diameter. 50 Any one of the preceding embodiments, comprising: 65. The adhesive mixture obtained by mixing component A and component B (preferably in a 1:1 volume ratio) has a D of about 20 microns. 50 Any one of the preceding embodiments, wherein the mixture comprises 50-70 wt. %, more preferably 55-68 wt. %, based on the total weight of the mixture, of aluminum hydroxide having the formula: 66. Component A is about 20 microns in diameter.50 Any one of the preceding embodiments, wherein the aluminum hydroxide has the formula: 67. Component B is about 20 microns in diameter. 50 Any one of the preceding embodiments, wherein the aluminum hydroxide has the formula: 68. Both components A and B have a D of about 20 microns. 50 Any one of the preceding embodiments, wherein the aluminum hydroxide has the formula: 69. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a thermal conductivity of at least 0.75 W / mK, more preferably at least 0.8 W / mK, after curing and standing for 7 days at 23° C. and 50% relative humidity, as measured according to ASTM D5470. 70. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength of 7.5 MPa or greater on an aluminum substrate after curing and standing for 7 days at 23° C. and 50% relative humidity, more preferably 8 MPa or greater, when measured according to the method set forth in the examples. 71. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 6 MPa or more, more preferably 8 MPa or more, and especially preferably 9 MPa or more, after curing and standing for 7 days at 23°C and 50% relative humidity, followed by cataplasm treatment for 7 days, as measured according to the method set forth in the examples. 72. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength of 8 MPa or greater, more preferably 9 MPa or greater, on an aluminum substrate after curing and storing for 7 days at 23° C. and 50% relative humidity, followed by storing for 168 hours at 85° C. and 85% relative humidity, when measured according to the method set forth in the examples. 73. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 8 MPa or greater, more preferably 9 MPa or greater, and especially preferably 10 MPa or greater, after curing and storing for 7 days at 23° C. and 50% relative humidity, followed by storing for 1,000 hours at 85° C. and 85% relative humidity, when measured according to the method set forth in the examples. 74. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity. 75. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B (at 23° C. and 50% relative humidity for 7 days) has a lap shear strength of 7.5 MPa or more, more preferably 8 MPa or more, on an aluminum substrate after curing for 7 days at 23° C. and 50% relative humidity and then standing, when measured according to the method set forth in the examples, and has a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity. 76. Any one of the preceding embodiments, wherein the cured adhesive (7 days at 23° C. and 50% relative humidity) has a lap shear strength of 6 MPa or more on an aluminum substrate after 7 days of Cataplasma treatment, as measured according to the method set forth in the Examples, more preferably 8 MPa or more, and most preferably 9 MPa or more, and has a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity. 77. Any one of the preceding embodiments, wherein the cured adhesive (7 days at 23° C. and 50% relative humidity) has a lap shear strength of 8 MPa or greater, more preferably 9 MPa or greater, on an aluminum substrate after 168 hours at 85° C. and 85% relative humidity, when measured according to the method set forth in the examples, and has a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity. 78. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B (at 23° C. and 50% relative humidity for 7 days) has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPa or more, after 1,000 hours at 85° C. and 85% relative humidity, as measured according to the method set forth in the examples, and has a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity. 79. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 7.5 MPa or greater, more preferably 8 MPa or greater, after curing and standing for 7 days at 23° C. and 50% relative humidity, when measured according to the method set forth in the examples, and a thermal conductivity of 0.75 W / mK or greater, more preferably 0.8 W / mK or greater, when measured according to ASTM D5470. 80. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 6 MPa or more, more preferably 8 MPa or more, and especially preferably 9 MPa or more, after curing and standing for 7 days at 23° C. and 50% relative humidity followed by cataplasm treatment for 7 days, when measured according to the method shown in the examples, and a thermal conductivity of 0.75 W / mK or more, more preferably 0.8 W / mK or more, when measured according to ASTM D5470. 81. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 8 MPa or greater, more preferably 9 MPa or greater, after curing and storing for 7 days at 23° C. and 50% relative humidity, followed by storing for 168 hours at 85° C. and 85% relative humidity, when measured according to the method set forth in the examples, and a thermal conductivity of 0.75 W / mK or greater, more preferably 0.8 W / mK or greater, when measured according to ASTM D5470. 82. Any one of the preceding embodiments, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPa or more, after curing and storing for 7 days at 23° C. and 50% relative humidity followed by storing for 1,000 hours at 85° C. and 85% relative humidity, when measured according to the method shown in the examples, and a thermal conductivity of 0.75 W / mK or more, more preferably 0.8 W / mK or more, when measured according to ASTM D5470. EXAMPLES

[0088] [Table 1]

[0089] Manufacturing of Liquid A (isocyanate component) The amounts of MDI, polyether polyol, and aminosilane (Dynasilan 1124) listed in Table 2 were first placed in a planetary mixer and mixed for 2 hours at room temperature with a mixing speed of 300-1,000 rpm, after which the fillers ATH, MPP, talc, carbon black, and amorphous silica were added to the mixture. The fillers were pre-dried in an oven at temperatures of 100-200 °C until the moisture level was less than 1,000 ppm. The fillers were mixed into the mixture for 30-60 minutes with a mixing speed of 1,000-2,000 rpm. The mixture was then filled into cartridges and stored.

[0090] Manufacture of B liquid (polyol component) The amounts of polyol, silane (Dynasilan), and catalyst shown in Table 2 were mixed at 500-1,000 rpm for 5-15 minutes, and then the fillers ATH, MPP, talc, amorphous silica, and molecular sieves were added to the mixture. The fillers were pre-dried in an oven at temperatures between 100-200 °C until the moisture level was less than 1,000 ppm. The fillers were mixed into the mixture at a mixing speed of 1,000-2,000 rpm for 30-60 minutes. The mixture was then filled into cartridges and stored.

[0091] Use of adhesives Parts A and B were mixed in a 1:1 volume ratio using a static mixer, which could then be applied to the substrate manually or robotically.

[0092] method flammable Adhesive samples were prepared by mixing parts A and B in a 1:1 volume ratio and curing the mixture at 23°C and 50% relative humidity for 7 days. The flammability of the samples was measured according to the UL94 flammability test. If burning ceased within 10 seconds on a vertical specimen, the sample was rated V0. Dripping of particles is acceptable as long as it does not burn. The results are reported in Table 2.

[0093] Thermal Conductivity Thermal conductivity was measured according to ASTM D5470. Three cured adhesive samples of three different thicknesses (1, 1.5, 2.5 mm) were prepared by mixing parts A and B in a static mixer and cured for 7 days at 23°C and 50% relative humidity, then cut into the target shape and size using a cutter. Thermal conductivity testing is performed according to ASTM D5470, and a thermal gel is applied between the test bar and the cured adhesive sample surface to minimize the interfacial thermal impedance due to trapped air. The set temperature of the sample is preferably 20-50°C, and the pressure applied to the sample is more than 0.5 MPa.

[0094] Lap Shear Test The lap shear strength was measured on aluminum alloy 3003 according to DIN EN1465. Aluminum substrates (AA6061 T6 1.92mm MF noPT no lub, 140x25mm, 1.9mm thick, from Novelis) were used. The substrates were cleaned with isopropanol before use. The adhesive was prepared by mixing parts A and B in a 1:1 volume ratio and applied to one substrate before bonding the second substrate within 5 minutes. The thickness was adjusted to 1.0mm and the overlap area was 25mmx25mm. The materials were cured and aged at 23°C and 50% relative humidity for 7 days before lap shear testing. The lap shear specimens were then mounted on a tensometer and lap shear tests were performed using a pulling speed of 10mm / min. The force deflection curves were observed. The strength at break was reported as lap shear strength.

[0095] Lap shear tests were performed immediately after curing, after 7 days of cataplasm exposure (cataplasm conditions were 70°C and 100% relative humidity for 7 days followed by a 24-hour thermal shock at -30°C), after 168 hours at 85°C and 85% relative humidity, and after 1,000 hours at 85°C and 85% relative humidity. The results are reported in Table 2.

[0096] [Table 2]

[0097] [Table 3]

[0098] All inventive and comparative examples not only had the desired UL94 flame retardant rating of V0, but also had acceptable thermal conductivity of greater than 0.75 W / mK. However, in comparative examples 4 and 5, the lap shear strength immediately after curing for 7 days at 23° C. and 50% relative humidity was significantly lower than the inventive examples. Similarly, comparative examples 4 and 5 showed a significant decrease in lap shear strength at all accelerated aging conditions, while inventive examples 1 and 2 showed no decrease in lap shear strength and even a slight increase in lap shear strength.

Claims

1. (A) (a1) a polyurethane prepolymer prepared from at least one polyol, at least one polyisocyanate, and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO sites; A first liquid comprising: (B) (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of said NCO moieties of (a1) with (b1); A second liquid containing A two-part flame retardant polyurethane adhesive formulation comprising: Part A and / or Part B contain aluminum hydroxide such that when Part A and Part B are mixed together to form the adhesive mixture (preferably in a 1:1 volume ratio), the aluminum hydroxide concentration is at least 50% by weight; A two-part flame retardant polyurethane adhesive formulation.

2. 1. A method for bonding two or more substrates, comprising the steps of: (1) (A) (a1) a polyurethane prepolymer prepared from at least one polyol, at least one polyisocyanate, and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO sites; A first liquid comprising: (B) (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of said NCO moieties of (a1) with (b1); A second liquid containing providing a two-part flame retardant polyurethane adhesive formulation comprising: Part A and / or Part B contain aluminum hydroxide such that when Part A and Part B are mixed together to form the adhesive mixture (preferably in a 1:1 volume ratio) there is an aluminum hydroxide concentration of at least 50% by weight; (2) mixing parts A and B to obtain an uncured adhesive; (3) applying the uncured adhesive to at least one substrate; (4) bringing the uncured adhesive into adhesive contact with a second substrate; (5) A step of curing the uncured adhesive The method includes:

3. (1) a first substrate; (2) a second substrate; a bonded assembly comprising: said first substrate and said second substrate being bonded together by a cured adhesive obtained by mixing together parts A and B; The solution A is (A) (a1) a polyurethane prepolymer prepared from at least one polyol, at least one polyisocyanate, and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO sites; A first liquid comprising: The B solution is (B) (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of said NCO moieties of (a1) with (b1); A second liquid comprising: A bonded assembly, wherein parts A and / or B contain aluminum hydroxide such that when parts A and B are mixed together to form an adhesive mixture (preferably a 1:1 volume ratio), the mixture is cured to provide an aluminum hydroxide concentration of at least 50% by weight.

4. 10. Any one of the preceding claims, wherein the polyisocyanate used in making the prepolymer is selected from aliphatic polyisocyanates, aromatic polyisocyanates, and mixtures thereof.

5. 10. Any one of the preceding claims, wherein the polyisocyanate used to prepare the prepolymer is selected from aromatic polyisocyanates.

6. 10. Any one of the preceding claims, wherein the polyisocyanate used in making the prepolymer is selected from methylene diphenyl diisocyanate (MDI), polycarbodiimide modified MDI, toluene diisocyanate (TDI), p-phenylene diisocyanate (PPDI), and naphthalene diisocyanate (NDI).

7. 13. Any one of the preceding claims, wherein the polyisocyanate used in making the prepolymer is MDI and / or polycarbodiimide modified MDI.

8. 10. Any one of the preceding claims, wherein the polyisocyanate used in the preparation of the prepolymer is used in an amount of 15 to 40 wt.-%, more preferably 17 to 35 wt.-%, particularly preferably 20 to 32 wt.-%, based on the total weight of component A.

9. 13. Any one of the preceding claims, wherein the prepolymer is prepared using 15 to 40 wt.-%, more preferably 17 to 35 wt.-%, particularly preferably 20 to 32 wt.-%, MDI and / or polycarbodiimide modified MDI, based on the total weight of component A.

10. 10. Any one of the preceding claims, wherein the polyol used to make the prepolymer is a polyether polyol.

11. The polyol used to prepare the prepolymer is a poly(alkylene oxide) diol (the alkylene group is C 2 ~C 6 and particularly preferably the alkylene group is C 2 ~C 4 Any one of the preceding claims comprising a polyol selected from:

12. 2. Any one of the preceding claims, wherein the polyol used to make the prepolymer comprises a polyol selected from poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols, and mixtures thereof.

13. 10. Any one of the preceding claims, wherein the polyol used to prepare the prepolymer comprises a polyol selected from poly(propylene oxide) polyols.

14. 2. The method of claim 1, wherein the polyol used to prepare the prepolymer comprises a propylene glycol-based polyether polyol capped with ethylene oxide having a molecular weight of about 2,000 Da and a functionality of 2.

15. 10. Any one of the preceding claims, wherein the polyether polyol used in the preparation of the prepolymer is used in an amount of 5 to 20 wt.-%, more preferably 8 to 15 wt.-%, particularly preferably 9 to 12 wt.-%, based on the total weight of component A.

16. 11. Any one of the preceding claims, wherein the polyol used for the preparation of the prepolymer is a polyether polyol based on propylene glycol and is used in an amount of 5 to 20 wt.-%, more preferably 8 to 15 wt.-%, particularly preferably 9 to 12 wt.-%, based on the total weight of component A.

17. 10. Any one of the preceding claims, wherein the final prepolymer has an NCO wt% in the range of 5 to 30 wt%, more preferably 10 to 25 wt%.

18. The aminosilane in component A is preferably represented by general formula I or general formula II: 【Chemistry 1】 (In the formula, R 1 is independent and C 1 ~C 6 alkyl; R 2 is independent and C 2 ~C 6 alkylene) 20. Any one of the preceding claims having the following:

19. The aminosilane in component A has the general formula I, R 1 C 1 ~C 2 alkyl, R 2 C 2 ~C 4 Any one of the preceding claims wherein is alkylene. In a more preferred claim, the aminosilane has the general formula I, R 1 is methyl, R 2 is propylene.

20. The aminosilane in component A has the general formula II, R 1 C 1 ~C 2 alkyl, R 2 C 2 ~C 4 Any one of the preceding claims wherein is alkylene.

21. The aminosilane has the general formula II, R 1 is methyl, R 2 Any one of the preceding claims, wherein is propylene.

22. 2. Any one of the preceding claims, wherein the aminosilane of component A is bis(trimethoxysilylpropyl)amine.

23. 5. Any one of the preceding claims, wherein the aminosilane in component A is preferably used in an amount of 0.5 to 4 wt.-%, more preferably 1 to 3 wt.-%, particularly preferably 1.5 to 2.5 wt.-%, based on the total weight of component A.

24. 10. Any one of the preceding claims, wherein the aminosilane in component A is bis(trimethoxysilylpropyl)amine and is used in an amount of 0.5 to 4 wt.-%, more preferably 1 to 3 wt.-%, particularly preferably 1.5 to 2.5 wt.-%, based on the total weight of component A.

25. The prepolymer in component A is from 15 to 40% by weight, more preferably from 17 to 35% by weight, particularly preferably from 20 to 32% by weight, of polyisocyanates, based on the total weight of component A; from 5 to 20% by weight, more preferably from 8 to 15% by weight, particularly preferably from 9 to 12% by weight, of polyether polyol, based on the total weight of component A; and 0.5 to 4% by weight, more preferably 1 to 3% by weight, particularly preferably 1.5 to 2.5% by weight, of aminosilane, based on the total weight of component A; Manufactured using any one of the preceding claims.

26. The prepolymer in component A is from 15 to 40% by weight, more preferably from 17 to 35% by weight, particularly preferably from 20 to 32% by weight, of MDI and / or polycarbodiimide-modified MDI or a mixture of MDI and polycarbodiimide-modified MDI, based on the total weight of component A; from 5 to 20% by weight, more preferably from 8 to 15% by weight and particularly preferably from 9 to 12% by weight, based on the total weight of component A, of polyether polyols based on propylene glycol, preferably polyether polyols based on propylene glycol having an OH number (mg KOH / g) of 109 to 115; 0.5 to 4% by weight, more preferably 1 to 3% by weight, particularly preferably 1.5 to 2.5% by weight, based on the total weight of component A, of aminosilanes of the general formula II, where R 1 is C 1 ~C 2 alkyl, R 2 is C 2 ~C 4 alkylene, more preferably R 1 is methyl, R 2 is propylene) Manufactured using any one of the preceding claims.

27. The prepolymer in component A is 20-32% by weight, based on the total weight of component A, of a mixture of MDI and polycarbodiimide-modified MDI; from 9 to 12 wt. %, based on the total weight of component A, of a propylene glycol-based polyether polyol having an OH number (mg KOH / g) of from 109 to 115; and 0.5 to 4% by weight, more preferably 1 to 3% by weight, and particularly preferably 1.5 to 2.5% by weight, of bis-(trimethoxysilylpropyl)amine, based on the total weight of component A. Manufactured using any one of the preceding claims.

28. 10. Any one of the preceding claims, wherein the polyol used in component B is a polyether polyol.

29. 13. Any one of the preceding claims, wherein the polyol used in component B has two or more OH groups.

30. The polyol used in component B is selected from poly(alkylene oxide) diols, the alkylene group being C 2 ~C 6 and particularly preferably the alkylene group is C 2 ~C 4 20. Any one of the preceding claims, wherein

31. 10. Any one of the preceding claims, wherein the polyol used in component B is selected from poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols.

32. 10. Any one of the preceding claims, wherein the polyol used in component B is selected from poly(propylene oxide) polyols.

33. 10. Any one of the preceding claims, wherein the polyol used in component B comprises a polyol selected from polyether diols.

34. 10. Any one of the preceding claims, wherein the polyether polyol of component B is a mixture of polyols having a functionality of 2 to 6.

35. 10. Any one of the preceding claims, wherein the polyether polyol of Component B is a mixture of at least one diol, at least one triol, and at least one polyol of functionality greater than 3.

36. 10. Any one of the preceding claims, wherein the polyether polyol of Component B is a mixture comprising or consisting of diols, triols, and polyols having a nominal functionality of 5 to 6.

37. 2. The method of claim 1, wherein the polyether polyol of Component B comprises a poly(propylene oxide) polyol having a functionality of 2.

38. 10. Any one of the preceding claims, wherein the polyether polyol of Component B is a mixture of poly(propylene oxide) polyols having a functionality of 2 to 6.

39. 10. Any one of the preceding claims, wherein the polyether polyol of Component B is a mixture comprising or consisting of at least one poly(propylene oxide) diol, at least one poly(propylene oxide) triol, and at least one poly(propylene oxide) polyol of functionality greater than 3.

40. 10. Any one of the preceding claims, wherein the polyether polyol of Component B is a mixture comprising or consisting of a poly(propylene oxide) diol, a poly(propylene oxide) triol, and a poly(propylene oxide) polyol having a nominal functionality of 5 to 6.

41. 10. Any one of the preceding claims, wherein the polyether polyol of Component B comprises 0 to 45 wt. % of a polyether triol, 0 to 30 wt. % of a polyether polyol having a functionality greater than 3, and 25 to 100 wt. % of a polyether diol, based on the total weight of the polyether polyols in Component B.

42. 10. Any one of the preceding claims, wherein the polyether polyol of Component B comprises 5 to 45 wt. % of a polyether triol, 10 to 35 wt. % of a polyether polyol having a functionality greater than 3, and 30 to 80 wt. % of a polyether diol, based on the total weight of the polyether polyols in Component B.

43. 13. Any one of the preceding claims, wherein the polyether polyol of Component B comprises 0 to 45 wt. % of a poly(propylene oxide) triol, 0 to 30 wt. % of a poly(propylene oxide) polyol having a functionality greater than 3, and 25 to 100 wt. % of a poly(propylene oxide) diol, based on the total weight of the polyether polyols in Component B.

44. 10. Any one of the preceding claims, wherein the polyether polyols in component B taken together are present in an amount of 15 to 50 wt.-%, more preferably 16 to 45 wt.-%, and especially preferably 18 to 42 wt.-%, based on the total weight of component B.

45. Component B comprises 15 to 50 wt. %, more preferably 16 to 45 wt. %, and particularly preferably 18 to 42 wt. %, based on the total weight of component B, of a mixture of polyether polyols, said mixture of polyether polyols comprising: (1) 30 to 45 weight percent of a polyether triol, 19 to 30 weight percent of a polyether polyol having a functionality greater than 3, and 27 to 40 weight percent of a polyether diol, based on the total weight of the polyether polyols in component B; or (2) 5 to 15 weight percent of a polyether triol, 10 to 25 weight percent of a polyether polyol having a functionality greater than 3, and 70 to 80 weight percent of a polyether diol, based on the total weight of the polyether polyols in component B; or (3) 100% by weight of a polyether diol, based on the total weight of the polyether polyols in Component B; or (4) 30 to 45 weight percent of a poly(propylene oxide) triol, 19 to 30 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 27 to 40 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols in component B; or (5) 5 to 15 weight percent of a poly(propylene oxide) triol, 10 to 25 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 70 to 80 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols in component B. Any one of the preceding claims comprising or consisting of the mixture (1), (2), (3), (4) or (5).

46. 10. Any one of the preceding claims, wherein component B comprises a diol and / or triol of molecular weight less than 200 Da, more preferably less than 150 Da.

47. Any one of the preceding claims, wherein component B comprises a butanediol (e.g., 1,4-butanediol).

48. 2. Any one of the preceding claims, wherein component B comprises glycerin.

49. 10. Any one of the preceding claims, wherein component B comprises 2 to 8 wt. %, more preferably 2.5 to 5 wt. %, of a diol or triol with a molecular weight of less than 200 Da, based on the total weight of component B.

50. 10. Any one of the preceding claims, wherein component B comprises butanediol (e.g. 1,4-butanediol) in an amount of 2 to 8 wt. %, more preferably 2.5 to 5 wt. %, based on the total weight of component B.

51. 10. Any one of the preceding claims, wherein component B comprises 2 to 8 wt. % glycerin, more preferably 2.5 to 5 wt. %, based on the total weight of component B.

52. 13. Any one of the preceding claims, wherein the catalyst is selected from Lewis bases and Lewis acids.

53. 13. Any one of the preceding claims, wherein the catalyst is selected from a tertiary amine, an organotin compound, and combinations thereof.

54. 2. Any one of the preceding claims, wherein the catalyst comprises diazabicyclo[2.2.2]octane.

55. 13. Any one of the preceding claims, wherein the catalyst comprises an organotin compound.

56. 13. Any one of the preceding claims, wherein the catalyst comprises di-n-octyltin bis(isooctylmercaptoacetate).

57. 5. Any one of the preceding claims, wherein the catalyst is used in an amount of 0.005 to 0.02 wt.-%, more preferably 0.0075 to 0.015 wt.-%, particularly preferably 0.01 wt.-%, based on the total weight of component B.

58. 5. Any one of the preceding claims, wherein the catalyst is di-n-octyltin bis(isooctylmercaptoacetate) and is used in an amount of 0.005 to 0.02 wt.-%, more preferably 0.0075 to 0.015 wt.-%, particularly preferably 0.01 wt.-%, based on the total weight of component B.

59. 10. Any one of the preceding claims, wherein the concentration of said aluminium hydroxide in the adhesive mixture obtained by mixing components A and B is 50-70 wt.-%, more preferably 55-68 wt.-%, based on the total weight of the mixture.

60. 10. Any one of the preceding claims, wherein the aluminium hydroxide is present in component A at 50 to 70 wt%, more preferably 55 to 68 wt%, based on the total weight of component A.

61. 10. Any one of the preceding claims, wherein the aluminium hydroxide is present in component B at 50 to 70 wt%, more preferably 55 to 68 wt%, based on the total weight of component B.

62. 13. Any one of the preceding claims, wherein the aluminum hydroxide is present in both component A and component B.

63. 10. Any one of the preceding claims, wherein the aluminium hydroxide is present in both component A and component B at 50 to 70 wt%, more preferably 55 to 68 wt%, based on the total weight of each component.

64. The aluminum hydroxide has a D of about 20 microns. 50 20. Any one of the preceding claims having the following:

65. The adhesive mixture obtained by mixing component A and component B (preferably in a 1:1 volume ratio) has a D of about 20 microns. 50 %.

66. Component A is about 20 microns D 50 % based on the total weight of component A, more preferably 55 to 68 wt. % of aluminum hydroxide having the formula:

67. Component B is about 20 microns D 50 % based on the total weight of component B, more preferably 55 to 68 wt. %.

68. Both component A and component B have a D of about 20 microns. 50 % by weight, more preferably 55 to 68% by weight, based on the total weight of each component.

69. 10. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B has a thermal conductivity of at least 0.75 W / mK, more preferably at least 0.8 W / mK, measured according to ASTM D5470, after curing and standing for 7 days at 23°C and 50% relative humidity.

70. 10. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 7.5 MPa or more, more preferably 8 MPa or more, when measured according to the method set out in the examples, after curing and standing for 7 days at 23°C and 50% relative humidity.

71. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B has, after curing for 7 days at 23°C and 50% relative humidity and then standing, followed by cataplasma treatment for 7 days, a lap shear strength on an aluminum substrate of 6 MPa or more, more preferably 8 MPa or more, particularly preferably 9 MPa or more, when measured according to the method shown in the examples.

72. 10. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, when measured according to the method set out in the examples, after curing and storing for 7 days at 23°C and 50% relative humidity, followed by storing for 168 hours at 85°C and 85% relative humidity.

73. 10. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, and particularly preferably 10 MPa or more, when measured according to the method set out in the examples, after curing and standing for 7 days at 23°C and 50% relative humidity, followed by standing for 1000 hours at 85°C and 85% relative humidity.

74. 10. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B has a UL 94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

75. 10. Any one of the preceding claims, wherein the cured (7 days at 23°C and 50% relative humidity) adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 7.5 MPa or more, more preferably 8 MPa or more, when measured according to the method shown in the examples after curing for 7 days at 23°C and 50% relative humidity and then standing, and has a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

76. 10. Any one of the preceding claims, wherein the cured (7 days at 23°C and 50% relative humidity) adhesive has a lap shear strength on an aluminium substrate of 6 MPa or more, more preferably 8 MPa or more, especially preferably 9 MPa or more, when measured according to the method shown in the examples, after 7 days of Cataplasma treatment, and has a UL94 rating of V0 after 7 days of curing at 23°C and 50% relative humidity.

77. 10. Any one of the preceding claims, wherein the cured adhesive (23°C, 50% relative humidity for 7 days) has a lap shear strength on an aluminum substrate of 8 MPa or greater, more preferably 9 MPa or greater, when measured according to the method set out in the examples after 168 hours at 85°C, 85% relative humidity, and has a UL94 rating of V0 after curing for 7 days at 23°C, 50% relative humidity.

78. 10. Any one of the preceding claims, wherein the cured (7 days at 23°C and 50% relative humidity) adhesive composition obtained by mixing components A and B has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, particularly preferably 10 MPa or more, measured according to the method shown in the examples after 1,000 hours at 85°C and 85% relative humidity, and has a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

79. 10. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B, after curing and standing for 7 days at 50% relative humidity, has a lap shear strength on an aluminum substrate at 23°C of 7.5 MPa or more, more preferably 8 MPa or more, when measured according to the method shown in the examples, and a thermal conductivity of 0.75 W / mK or more, more preferably 0.8 W / mK or more, when measured according to ASTM D5470.

80. 10. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B, after curing and standing for 7 days at 23°C and 50% relative humidity and subsequent cataplasma treatment for 7 days, has a lap shear strength on an aluminum substrate of at least 6 MPa, more preferably at least 8 MPa, and particularly preferably at least 9 MPa, when measured according to the method shown in the examples, and a thermal conductivity of at least 0.75 W / mK, more preferably at least 0.8 W / mK, when measured according to ASTM D5470.

81. 10. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B, after curing and standing for 7 days at 23°C and 50% relative humidity followed by standing for 168 hours at 85°C and 85% relative humidity, has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, when measured according to the method set out in the examples, and a thermal conductivity of 0.75 W / mK or more, more preferably 0.8 W / mK or more, when measured according to ASTM D5470.

82. 10. Any one of the preceding claims, wherein the cured adhesive composition obtained by mixing components A and B, after curing and standing for 7 days at 23°C and 50% relative humidity and subsequently standing for 1,000 hours at 85°C and 85% relative humidity, has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, and particularly preferably 10 MPa or more, when measured according to the method shown in the examples, and a thermal conductivity of 0.75 W / mK or more, more preferably 0.8 W / mK or more, when measured according to ASTM D5470.

Citation Information

Patent Citations

  • Bi-component polyurethane heat-conducting structural adhesive and preparation method thereof

    CN113736419A

  • Moisture-curable polyurethane hot-melt resin composition

    JP2021042293A

  • High-strength silane-modified polymer adhesive composition

    JP2022512246A

  • Thermal interface material

    WO2022056096A1